O-GlcNAcylation of a circadian clock protein: dPER taking its sweet time - Diernfellner, Axel; Brunner, Michael (Genes & development, 2012)
In this issue of Genes & Development, Kim and colleagues (pp. 490-502) report that the Drosophila circadian repressor dPER undergoes O-linked GlcNAcylation (O-GlcNAc). Their data show that manipulation of the relevant O-GlcNAc transferase (OGT) regulates behavioral rhythmicity by affecting the stability and nuclear translocation of dPER.